Modern information and communication technologies in education and artificial intelligence: prospects and practical solutions - Zuparova, Munira (MMIT Proceedings, 2025)
This article analyzes the possibilities of information and communication technologies (ICT) and artificial intelligence (AI) in the modern education system. Attention is paid to the importance of increasing the effectiveness of education using ICT tools, introducing individual training and assessment systems based on AI. In particular, the advantages of distance learning, digital platforms, virtual teachers, and approximate analysis methods are considered through examples.